Предмет: Математика,
автор: Valeriy2002Nin
Помогите с заданием на фотографии!
Приложения:
Ответы
Автор ответа:
1
11.
а)(2х + 1) + 3х = 11 б)(х - 5) - ( 2 - 2х) = 6
2х + 1 + 3х = 11 х - 5 - 2 + 2х = 6
2х + 3х = 11 - 1 х + 2х = 6 + 5 + 2
5х = 10 3х = 13
х = 10 : 5 х = 13 : 3
х = 2 х ≈ 4
а)(2х + 1) + 3х = 11 б)(х - 5) - ( 2 - 2х) = 6
2х + 1 + 3х = 11 х - 5 - 2 + 2х = 6
2х + 3х = 11 - 1 х + 2х = 6 + 5 + 2
5х = 10 3х = 13
х = 10 : 5 х = 13 : 3
х = 2 х ≈ 4
Похожие вопросы
Предмет: Английский язык,
автор: гога53
Предмет: Английский язык,
автор: plalisa
Предмет: Русский язык,
автор: зия71
Предмет: Английский язык,
автор: Nasrechkaa
Предмет: Алгебра,
автор: dejhjhjjdfhdufd